The Awareness posters and their role in the face of intellectual extremism" Analytical sociological study" - Dalala, Mirna (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
Conventional wisdom maintains that images hold “power” to sway public opinion, to move us to action and to ultimately “change history.” The Directional poster is one of the images of the advertisement, which aims to spread the message by convincing the public and encouraging it to accept a range of ideas and information. It also plays a major role in the development of the cultural, social and political awareness of individuals and contributes to raising the public taste. It is a creative value with visual and emotional qualities. On the other hand, the phenomenon of intellectual extremism is one of the important problems that deserve to be studied, because it poses a real danger to all societies. Aaccordingly, this study aimed to emphasize the role of advertising poster on the one hand; and its role in facing the most serious problem faced by societies, namely intellectual extremism. Therefore, the problem of research on how to activate the role of advertising poster awareness in the development of awareness of visual culture, and activate its role also in the face of extremism and the dissemination of cultural awareness and community to accept the other. The research is based on the premise that the advertising poster can be used to change the individual’s culture towards accepting the other and confronting extremism.